555 Profile and burden chronic disease patients' caregivers followed by a homecare service in brazil – a cross-sectional study. (24th April 2018) - Fregonezi, RL; Neves, EWJC; Ferreira, LR; Barbosa, JG
Abstract : Introduction: Caregiver burden is a discomposure (physical, psychological, social, or financial) in dealing with person's disability and dependence on care. The progressive ageing of the population promoted by the demographic transition and the advent of chronic-degenerative diseases increasingly show the role of caregiver as a profession, together with the need to evaluate repercussions for their well-being and health by caring. In comparison the formal and informal caregivers, the concerns with regard to quality of life was similar. The objective of the study was to evaluate the caregiver's profile and establish a relation among the more intense burden and the degree of elderly's dependence. Methods: A descriptive cross-sectional study with 157 caregivers and 159 patients (February-September 2016) was carried out with a Preventive Medicine Program, a systematised home care service (HCS) at Unimed Health Operator, in Poços de Caldas-MG. The burden of caregivers was evaluated using Zarit Burden Interview (ZBI); to evaluate self-care capacity, the Palliative Performance Scale (PPS) was applied. Statistical analysis was performed using the Mann-Whitney test, using p<0.05. Results: Patients were divided in 2 groups (87% PPS <60, 13% PPS >60, average PPS=48.89), demonstrating that most patients were highly care dependent. 42, 5% of the caregivers have moderate-intense burden for the more dependent patient's group with PPS ≤60 compared to only 2.5% with moderate burden in less dependent group of patients with PPS >60 (p<0, 001). Average ZBI=46.36; Impact on care=40%; Interpersonal relationship=32%; Expectation with care=61%; Perceived self-efficacy=51%. Caregiver profile: mostly female (mean age=58 years-old); the burden is only influenced by the level of dependency of the patient (p<0, 001). Discussion: There is a moderate-severe burden for caregiver's patients assisted by Unimed's HCS, and this was directly related to the level of dependence measured by PPS. These data is in accordance to a Portuguese study, which identified a moderate-intense burden in 37.2% of the caregivers.